Standards in English Education : An Enduring Historical Issue - Crook, David (Revista Española de Educación Comparada, 2011)
This article closely examines the development of education in England, taking special account of educational standards —of the official measurable kind, but also the perceived kind— in the various sectors of education.It argues that, today, and in the past, the ‘problems’ associated with education standards mostly relate to a ‘long tail’ of under performing schools serving urban areas and attended by relatively under privileged children. At the other end of the scale, it issuggested that England’s leading schools, both in the public and private sectors,remain the subject of admiration. The same remains true of England’s leading, and typically oldest, universities, which occupy a more privileged position than institutions chartered in the relatively recent past. The article presents a story of persistent unequal educational opportunities overtime, which, worryingly,does not seem to be improving in the second decade of the twenty-firstcentury. Este artículo examina de cerca el desarrollo de la educación en Inglaterra teniendo especialmente en cuenta los estándares educativos —tanto en sus medidas oficiales como en sus valores percibidos— en los distintos sectores de la educación. Argumenta que, aún hoy, y en el pasado, los «problemas» asociados con los estándares educativos se relacionan principalmente con cierto número de escuelas con bajo rendimiento y ubicadas en áreas suburbanas a las que asisten alumnos desfavorecidos. En el otro extremo de la escala se sugiere que las escuelas líderes inglesas tanto en el sector público como en el privado se mantienen como objetos de admiración. En el mismo sentido le ocurre a las universidades inglesas más tradicionales que ocupan una posición mucho más privilegiada que otras instituciones establecidas en el pasado reciente. El artículo ofrece una panorámica de permanentes inequidad de las oportunidades educativas que, preocupantemente, no parece haber mejorado en la segunda década del s. XXI.